NAD-malic enzymes of Arabidopsis thaliana display distinct kinetic Q1 mechanisms that support differences in physiological control - Tronconi, Marcos Ariel (2010)
The Arabidopsis thaliana genome contains two genes encoding NAD-MEs [NAD-dependent malic enzymes; NAD-ME1 (TAIR accession number At4G13560) and NAD-ME2 (TAIR accession number At4G00570)]. The encoded proteins are localized to mitochondria and assemble as homo- and heterodimers in vitro and in vivo. In the present work, the kinetic mechanisms of NAD-ME1 and -ME2 homodimers and NAD-MEH (NAD-ME heterodimer) were studied as an approach to understand the contribution of these enzymes to plant physiology. Productinhibition and substrate-analogue analyses indicated that NADME2 follows a sequential ordered Bi-Ter mechanism, NAD being the leading substrate followed by L-malate. On the other hand, NAD-ME1 and NAD-MEH can bind both substrates randomly. However, NAD-ME1 shows a preferred route that involves the addition of NAD first. As a consequence of the kinetic mechanism, NAD-ME1 showed a partial inhibition by L-malate at low NAD concentrations. The analysis of a protein chimaeric for NAD-ME1 and -ME2 indicated that the first 176 amino acids are associated with the differences observed in the kinetic mechanisms of the enzymes. Furthermore, NAD-ME1, -ME2 and -MEH catalyse the reverse reaction (pyruvate reductive carboxylation) with very low catalytic activity, supporting the notion that these isoforms act only in L-malate oxidation in plant mitochondria. The different kinetic mechanism of each NAD-ME entity suggests that, for a metabolic condition in which the mitochondrial NAD level is low and the L-malate level is high, the activity of NAD-ME2 and/or -MEH would be preferred over that of NAD-ME1.